2017
DOI: 10.1016/j.ejca.2017.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Response rate as a potential surrogate for survival and efficacy in patients treated with novel immune checkpoint inhibitors: A meta-regression of randomised prospective studies

Abstract: The results of the trial-based meta-regression analysis indicated a weak correlation between RR and OS, supporting future investigations to assess the surrogacy of RR in the patient treated with immune checkpoint inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Through article searching, we found 19 articles in PubMed and one eligible meta-analysis by hand searching; among those 20 articles, five were not meta-analyses that evaluated the association of OS and other endpoints, three were meta-analyses but without association results for immunotherapies, and one was a meta-analysis for immunotherapies but it was conducted based on individuallevel analysis. Therefore, a total of 11 studies were eligible according to our inclusion/exclusion criteria (Figure 1) (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). In these studies, surrogate endpoints included PFS (20,21,(23)(24)(25)(26)(27)(28)(29)(30), three-month PFS (29), 6-month PFS (20,23,29), ORR (20)(21)(22)(23)(24)(25)27,28), disease control rate (DCR) (23,24), 1-year survival (26,28,30) and 2-year survival (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through article searching, we found 19 articles in PubMed and one eligible meta-analysis by hand searching; among those 20 articles, five were not meta-analyses that evaluated the association of OS and other endpoints, three were meta-analyses but without association results for immunotherapies, and one was a meta-analysis for immunotherapies but it was conducted based on individuallevel analysis. Therefore, a total of 11 studies were eligible according to our inclusion/exclusion criteria (Figure 1) (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). In these studies, surrogate endpoints included PFS (20,21,(23)(24)(25)(26)(27)(28)(29)(30), three-month PFS (29), 6-month PFS (20,23,29), ORR (20)(21)(22)(23)(24)(25)27,28), disease control rate (DCR) (23,24), 1-year survival (26,28,30) and 2-year survival (30).…”
Section: Resultsmentioning
confidence: 99%
“…• 5 were not a meta-analysis evaluating the association of OS and other endpoints • 3 were meta-analyses but without association results for immunotherapies • 1 was a meta-analysis for immunotherapies but was conducted by individual-level analysis 11 of eligible meta-analyses For statistical method, even though correlation analysis and/or linear regression were used, our included metaanalyses performed them not in an exactly same way: most meta-analyses (82%; 9/11) were weighted by sample size (20)(21)(22)(23)(24)(25)(26)(27)30); among them, four meta-analyses performed the statistics on a logarithmic scale (21,22,26,30), and two conducted adjustment in linear regression model (23,26). For association results, six meta-analyses had evaluation criteria for considering validated endpoint surrogacy for OS, including R 2 ≥0.80 (21), R 2 ≥0.75 (24), R 2 ≥0.72 (23), R 2 ≥0.64 (28,30), and R 2 ≥0.60 (26).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the use of ORR as a surrogate endpoint for OS in trials with ICI remains an unsolved question. A meta regression analysis of seventeen randomized trials testing ICI showed a weak but statistically significant correlation between the treatment effect on the ORR and the treatment effect on survival outcomes (i.e., OS and PFS) and suggested that the activity of ICI in terms of ORR explain ~50% of the effects detected in survival (29). Conversely, a systematic review of ten clinical trials evaluating PD-1/PD-L1 inhibitors in advanced NSCLC failed to show a significant correlation between response and survival (30).…”
Section: Objective Overall Response Ratementioning
confidence: 99%
“…However, since this meta-analysis analysed only three RCTs, it is not possible to conclude that ICIs do not work in pre-treated metastatic GC. In addition, it should be considered that endpoints, such as PFS and response rate (RR), are not optimal in patients treated with ICIs [18].…”
Section: Discussionmentioning
confidence: 99%